2018
DOI: 10.5194/amt-11-1901-2018
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of formic acid, acetic acid and hydroxyacetaldehyde, hydrogen peroxide, and methyl peroxide in air by chemical ionization mass spectrometry: airborne method development

Abstract: Abstract. A chemical ionization mass spectrometry (CIMS) method utilizing a reagent gas mixture of O2, CO2, and CH3I in N2 is described and optimized for quantitative gas-phase measurements of hydrogen peroxide (H2O2), methyl peroxide (CH3OOH), formic acid (HCOOH), and the sum of acetic acid (CH3COOH) and hydroxyacetaldehyde (HOCH2CHO; also known as glycolaldehyde). The instrumentation and methodology were designed for airborne in situ field measurements. The CIMS quantification of formic acid, acetic acid, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…We have normalized their predicted sensitivities to − ( ) and the relative sensitivities are 1.000, 0.034, 0.007, and 0.001for − ( ), − ( ), − ( 2 2 ), and − ( 3 ), respectively. This ranking is consistent with the observations of O'Sullivan et al (2017) in which they noted observing − ( 2 2 ) but not − ( 3 ) clusters with the PCIMS instrument and with Treadaway et al (2017) in which they observed a weak standard addition calibration signal for − ( 3 ) in the laboratory and during FRAPPE (Treadaway et al, 2017;Fig. 3).…”
Section: Iodidesupporting
confidence: 91%
“…We have normalized their predicted sensitivities to − ( ) and the relative sensitivities are 1.000, 0.034, 0.007, and 0.001for − ( ), − ( ), − ( 2 2 ), and − ( 3 ), respectively. This ranking is consistent with the observations of O'Sullivan et al (2017) in which they noted observing − ( 2 2 ) but not − ( 3 ) clusters with the PCIMS instrument and with Treadaway et al (2017) in which they observed a weak standard addition calibration signal for − ( 3 ) in the laboratory and during FRAPPE (Treadaway et al, 2017;Fig. 3).…”
Section: Iodidesupporting
confidence: 91%
“…We used a source tracer analysis to investigate the likely role of biogenic versus anthropogenic sources in driving model biases for key oxygenated VOCs. Table S1 (O'Sullivan et al, 2018;Treadaway et al, 2018;Lerner et al, 2017;Min et al, 2016;Müller et al, 2016b;Cazorla et al, 2015;Richter et al, 2015;Lee et al, 2014;Müller et al, 2014;Yacovitch et al, 2014;Kaser et al, 2013;DiGangi et al, 2011;Fried et al, 2011;Zheng et al, 2011;Apel et al, 2010;Pollack et al, 2010;St Clair et al, 2010;Weibring et al, 2010;Wooldridge et al, 2010;Gilman et al, 2009;Hottle et al, 2009;Osthoff et al, 2008;de Gouw and Warneke, 2007;Huey, 2007;Kim et al, 2007;Crounse et al, 2006;Slusher et al, 2004;Blake et al, 2003;Schauffler et al, 2003;Wisthaler et al, 2002;Colman et al, 2001;Ryerson et al, 1999;Ryerson et al, 1998;Weinheimer et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these materials can cause the formation of CO2 and CH4 gases. Acetic acid CH3COOH which is oxygenated into volatile organic compounds is found in remote and urban environments in the form of gases and particles [15].…”
Section: Life Cycle Impact Assessmentmentioning
confidence: 99%